Evaluation Of The Use Of Cyclophosphamide In Children Diagnosed With Steroid Resistant Nephrotic Syndrome Treated In The 3rd Floor Treatment At Fatmawati Hospital - Sinukaban, Satriani; Setiadi Darmawan, Bobby (Jurnal Farmasi Klinik Best Practice, 2022)
A total of 32 children with nephrotic syndrome were treated with cyclophosphamide, the remissions and side effects that often occurred during therapy were counted. This research was conducted using a retrospective descriptive method. The results showed that the remission was 59.4%. The mean duration of the call to remission was 14 weeks and the mean dose of cyclophosphamide was 589 mg. As many as 59.4% of patients experienced no side effects, while 40.6% experienced side effects. Side effects that occurred included vomiting (3.1%); nausea (3.1%); hair loss (6.3%); nausea and vomiting (12.5%); vomiting and hair loss (6.3%); nausea and hair loss (6.3%); and nausea, vomiting, and hair loss (3.1%). Keywords: Steroid-Resistant Nephrotic Syndrome, Cyclophosphamide